2014
DOI: 10.5267/j.msl.2013.12.013
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation on relationship between social capital and organizational commitment

Abstract: This paper presents an empirical investigation to study the relationship between social capital and organizational commitment. The study considers the relationship between social capital with three components of organizational commitment; namely, affective commitment, continuous and normative commitment. The study has been applied among a sample of 292 regular employees who worked for an Iranian bank located in city of Tehran, Iran. The implementation of Pearson correlation has indicated that there were positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…Moreover, in-service training positively influence on psychological empowerment. The results of this study are consistent with other studies (Bani et al, 2014;Alikhani et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, in-service training positively influence on psychological empowerment. The results of this study are consistent with other studies (Bani et al, 2014;Alikhani et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…They reported that psychological empowerment of employees could influence on organizational learning characteristics in organization, significantly. Alikhani et al (2014) studied the relationship between social capital and organizational commitment by considering the relationship between social capital with three components of organizational commitment; namely, affective commitment, continuous and normative commitment. They stated that there were positive and meaningful relationships between social capital and affective commitment, continuous and normative commitment.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Pillai et al (2017) asserted that social capital has its own disadvantage on some individual and organizational outcomes, and the non-significant findings of this study are not surprising. Further, in the case of commitment, the finding is also corroborated with the previous findings (Aküzüm & Tan, 2014;Alikhani et al, 2014;Brien et al, 2015;Chang et al, 2018) and according to Ellison et al (2007), greater access to social capital rises commitment and individual capability to organise collective actions.…”
Section: Assessment Of Structural Modelsupporting
confidence: 87%
“…The results of the data analysis indicated that psychological empowerment of employees could impact on organizational learning aspects in organization, significantly. Alikhani et al (2014) presented an empirical survey to study the relationship between social capital and organizational commitment. The study considered the relationship between social capital with three components of organizational commitment; namely, affective commitment, continuous and normative commitment.…”
Section: Introductionmentioning
confidence: 99%